الإنفاق العام ودوره التنموي في الاقتصاد السوري - صقر, محمد; شرف, سمير; غدير, هيفــاء غدير (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتوقف هذا البحث عند سياسة الإنفاق العام كجزء من السياسة المالية لها دورها في عملية التنمية الاقتصادية، ويظهر الدور الذي لعبته هذه السياسة (بشقيها الجاري والاستثماري) في المراحل التي مر بها الاقتصاد السوري، كما يقوم بدراسة الدعم الحكومي والرواتب والأجور كوجهين من أوجه الإنفاق العام, ويتوقف بذلك عند التحديات التي تواجه سياسة الدعم، كما يتوقف عند ضرورة دراسة سياسة الرواتب والأجور دراسة دقيقة وعلمية وحل جميع المشكلات المتعلقة بها. وأخيراً تم التوقف عند الإصلاحات الواجب القيام بها لتقوم سياسة الإنفاق العام بدورها كأداة مالية دافعة لعملية التنمية الاقتصادية، من ضرورة التنسيق بين الجهات المسؤولة عن الإنفاق العام، إلى العمل بمبدأ إنتاجية النفقة، والإسراع بتفعيل سوق الأوراق المالية في سورية، وتطوير الأجهزة المصرفية والمالية. This research studies the general expenditure policy as a part of financial policy which has its role in the economic development. It shows the role of this policy (current and investment) in the stages of the Syrian economy. It also studies the government support, the salaries and wages as two aspects of the general expenditure, and illustrated the challenges of the support policy. It also focused on the need to study the policy of salaries and wages scientifically and solve all the related problems. Finally, the research focused on the necessary reforms to evaluate the general expenditure policy to take its role as a financial support for the economic development, such as the coordination between the responsible authorities of the general expenditure, adopt the concept of expenses' productivity, and set out the money market in Syria, and develop the financial and banking institutions.